The Association of Early and Recent Psychosocial Life Stress With Leukocyte Telomere Length. Issue 8 (October 2015) - Verhoeven, Josine E.; van Oppen, Patricia; Puterman, Eli; Elzinga, Bernet; Penninx, Brenda W.J.H.
ABSTRACT: Objectives: Chronic exposure to psychosocial stressors is related to worse somatic health. This association applies both to stressors early in life, such as childhood adversities, and more recent life stress, such as stressful life events. This study examined whether accelerated telomere shortening, as an indicator of cellular aging, might be an explanatory mechanism. Methods: We examined whether childhood adversities and recent stressful life events were associated with shorter telomeres in 2936 participants (mean [standard deviation] age = 41.8 [13.1] years, 66% women, 57% current depression) of the Netherlands Study of Depression and Anxiety. Telomeres are specialized nucleic acid–protein complexes at the ends of linear DNA that shorten with age; telomere length (TL) was measured with quantitative polymerase chain reaction. Results: Childhood life events ( β = .004, p = .805) and childhood trauma ( β = −.023, p = .205) were not related to shorter TL. However, we found negative associations between recent stressful life events and TL. Persons had shorter telomeres if they reported more stressful life events in the past year ( β = −.039, p = .028) and 1 to 5 years ago ( β = −.042, p = .018, adjusted for sociodemographics). The relationship between stressful life events and TL became borderline significant when further adjusted for smoking status. No associations with TL were found when stressful life events occurred more than 6 years ago ( p > .10). Conclusions: Results show that recent stressful life events are associated with shorter TL. This association is not observed for psychosocial stressors that occur earlier in life. Whether these results are indicative of physiological resiliency remains to be explored by future longitudinal research.